Congenital Diaphragmatic Hernia: A Benin Teaching Hospital Experience - BAGNAN-TOSSA, LÉHILA; noukpozounkoun, brubo; Mewanou, Serge (My University, 2018)
Congenital diaphragmatic hernia is the outcome of the abdominal contents in the thorax by a breach caused by a failure to close the pleuroperitoneal canal. It is a rare and serious disease. Our teaching hospital had registered these seven last years five cases of congenital diaphragmatic hernia, operated, but never published. We report the most recent one, a case of a newborn baby seen at the 5th hour of life for respiratory distress. Initial examination revealed: an asymmetric thorax, respiratory distress with 88% oxygen saturation at ambient air, tachycardia and abolition of vesicular murmur in the left lung field. L-abdomen was flat and soft. Thoraco-abdominal radiography revealed a clear left intra-thoracic image with mass effect on the left lung parenchyma. He has benefited from a reduction of the herniated visceras and a successful closing of the breach. The operation had few after-effects after five months follow-up with a very good recovery of the cardio-pulmonary function.
Keywords: Hernia; Diaphragmatic; Congenital